Model Service Psychology In SDMT Ponorogo - Deppy Aulia Pratiwi; Mellynda Fibiani; Shelia Gian Wardhana; Yusuf Hamdani Abdi; Devid Dwi Erwahyudin (Jurnal Multidisiplin Sahombu, 2024)
This article highlights the importance of psychology services at Muhammadiyah Terpadu Ponorogo Primary School in assisting children's holistic development. The research describes the school's psychology service model, emphasizing collaboration between teachers, psychologists, and parents in addressing complex issues involving students' families. Although there are still constraints related to time and access, psychological services at SDMT Ponorogo are considered to have a positive impact on students' development, especially in addressing social issues such as bullying. The article also discusses the unique characteristics of primary school-age children and the important role of character education in addition to intellectual abilities. With psychological services, schools can play an active role in guiding students, ensuring safety and comfort in the learning environment, and creating effective collaboration between schools, psychologists, teachers, and parents.